TINJAUAN PENGENDALIAN HAMA TIKUS PADA TANAMAN PADI MA’HAD AL-ZAYTUN PERSPEKTIF UNDANG-UNDANG NOMOR 32 TAHUN 2024 DAN MAQASHID SYARIAH - Sodikin, Ali; Rohmah, Siti Ngainnur; Sajali, Munawir (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Food is a basic need and a human right essential for national stability. Rice, as the primary source, plays a strategic role in Indonesia’s food security. Rice production declined in 2021 due to land degradation, climate change, and pest attacks, particularly the rice field rat, which is the most destructive pest. This study evaluates ecologically based rat pest control in accordance with Law No. 32 of 2024 and the principles of maqashid sharia at Ma’had Al-Zaytun, which implements sustainable agriculture, to provide effective recommendations for increasing rice productivity and preserving the ecosystem. The purpose of this study is to examine rat pest control in rice fields at Ma’had Al-Zaytun from the perspective of Law No. 32 of 2024 and Maqashid Sharia. This research uses a normative legal approach or literature study. The data used include primary sources: Law No. 32 of 2024, the book "Bioecology and Control of Rice Field Rats" by Sudarmaji, the book "Hifdh Al-Bi’ah as part of Maqasid Al-Shari’ah: Yusuf Al-Qardawy’s perspective on the environment in Ri’ayat al-Bi’ah fi Shari’ah al-Islam book" by Ahmad Sarip Saputra, et al., the book "Panorama Maqashid Syariah" by Dr. Sutisna et al., and the book "Al-Zaytun Sumber Inspirasi" by Drs. Ch. Robin Simanullang, as well as Al-Zaytun Magazine, edition 49, 2008, and the book "Mengenal Aneka Komoditas Tanaman Pertanian di Ma’had Al-Zaytun" by Sobirin, S.P., M.Pd., et al., and strengthened by secondary data, namely journals, books, and related articles. Data were collected through finding, organizing, and editing techniques, then analyzed using content analysis methods. To ensure data validity, triangulation, member checking, and expert opinion were used. The results of this study are: (1) Control of rat pests in rice plants at Ma’had Al-Zaytun from the perspective of Article 4 of Law Number 32 of 2024 is through a strategy of conserving biological resources and ecosystems for controlling rat pests. This practice not only reflects institutional ecological awareness, but also demonstrates a model of sustainable agricultural practices that integrate biological conservation principles with the national legal framework. (2) Control of rat pests in rice plants at Ma’had Al-Zaytun from the perspective of Maqashid Syariah is by implementing hifdz al-nafs, namely protecting humans from health risks, and hifdz al-bi’ah, namely preserving the environment through a non-chemical approach. In other words, this practice is a concrete form of actualizing Islamic teachings in a sustainable agricultural system